Managing Rewards to Enhance Customer Value: Empirical Study of Frequent Flyer Program - Kristiani, Enny; Sumarwan, Ujang; Yuliati, Lilik Noor; Saefuddin, Asep (Jurnal Manajemen Teknologi, 2014)
Abstract. The goal of relational program is to retain customers who are profitable to the organization. Reward point is a form of customer loyalty widely used by many industries including airline industry. Airline loyalty program, notorious as Frequent Flyer Program (FFP), is the most sophisticated marketing strategic used by airline industries nowadays. However most airlines have very little understanding of their FFP members yet have a little knowledge about their most valuable customers. Most airlines have inaccurately determined the customer values by only considering business worth of nominal profit generated by FFP members. The value of customers beyond purchasing behavior - called relational worth - has not been commonly captured yet. This non-financial value is predicted as a driver in retaining customers, hence becomes one of crucial factors in preserving the profitability of the organization. For this reason, this paper aims to examine the customer non-financial valuations of FFP members to the airline. The hypotheses are empirically tested with a sample of FFP members of respected airline conducted through online survey (n=475). The data were statistically analyzed using structural equation modeling (SEM). Results indicate that perceived rewards generate higher value of relational worth through indirect relationship by intervening variable of relationship quality than that of generated by a direct relationship.Keywords:Frequent Flyer Program,Customer Relationship Management (CRM), Loyalty Reward Program, Relationship Quality, Relational worth Abstrak. Program loyalitas dilakukan oleh perusahaan dengan tujuan untuk mempertahankan pelanggan yang menguntungkan. Program ini biasanya ditawarkan dengan memberikan insentif (hadiah) kepada pelanggan, seperti pada program Frequent Flyer (FFP) di bisnis penerbangan. Pada umumnya maskapai penerbangan masih belum dapat mengidentifikasi dengan benar pelanggan-pelanggan yang berharga. Pelanggan yang bernilai tinggi masih ditentukan hanya berdasarkan nilai ekonomis (berapa banyak uang yang dibelanjakan pelanggan terhadap maskapai) dan belum mempertimbangkan nilai-nilai sosial pelanggan yang diberikan kepada maskapai. Nilai sosial ini merupakan salah satu penentu keuntungan perusahaan. Penelitian ini bertujuan untuk mengetahui pengaruh hadiah yang diberikan kepada pelanggan melalui program loyalitas terhadap nilai relasional yang dihasilkan. Hipotesa diuji dengan menggunakan sampel yang terdiri dari 475 anggota FFP yang diperoleh dengan melalui survey online. Data dianalisis secara statistik dengan Stuctural Equation  Modelling (SEM). Hasil penelitian menunjukkan pengaruh signifikan insentif yang diberikan melalui FFP terhadap nilai sosial pelanggan. Hadiah yang menyebabkan timbulnya perasaan komitmen dan kepuasan pada pelanggan akan menghasilkan nilai sosial yang lebih tinggi.Kata kunci : Frequent Flyer Program, Manajemen Relasional Konsumen, Program Loyalitas, Kualitas Hubungan, Nilai Relasional